30-Year Spatial-Temporal Analysis of Air Surface Temperature as Climate Change Mitigation - Adi Wibowo; Tia Pramudyasari; Suko Prayitno Adi; Ratna Saraswati; Iqbal Putut Ash Shidiq (Indonesian Journal of Geography, 2022)
Natural and anthropogenic factors, such as volcanic eruptions and land use, are indirect causes of changes in the micro-scale climate. Over the past 30 years, climate change has been detected with increased air surface temperature (AST) above 30.00C, a phenomenon of Urban Heat Island. Therefore, this study aimed to create a spatial model to see changes in AST in Bandar Lampung City from1990 to 2020. The spatial and temporal analysis uses Landsat data to produce land surface temperature (LST) and AST models. The results showed a temperature rise in the LST area, which tends to be the northern part of Bandar Lampung City, by 25.0oC and above for 30 years. Compare LST and AST from two stations between 30 years is 5.00C. In 1990, the LST concentrated on the spatial distribution of the AST model with a temperature above 30.00C, while in 2020, it diffused to the northern part of Bandar Lampung City. The results concluded that the air temperature in the city has warmed up to 0.46OC (+10C), which is in line with the findings of IPPC and various world cities. It is also in occurrence with the UHI phenomenon since 2014 that climate change is part of mitigation.